Ambazonian or Cameroonian? Perceived Discrimination and National Identification Among Anglophones in Cameroon - Elvis Nshom (Social Sciences, 2025)
This study focuses on the ongoing conflict in Cameroon between Anglophone separatist fighters and the predominantly Francophone government over the marginalization and discrimination of Anglophones in Cameroon and the creation of an independent state called the Republic of Ambazonia. This study seeks to understand the extent to which perceived discrimination explains national identification with the Republic of Cameroon and national identification with the so-called Republic of Ambazonia. In a sample of 314 participants, the results showed that there was no significant difference between national identification with the Republic of Cameroon and national identification with the Republic of Ambazonia. In addition, perceived personal discrimination and perceived group discrimination were positively associated with national identification with the Republic of Ambazonia but negatively associated with national identification with the Republic of Cameroon. Lastly, there was a negative correlation between national identification with the Republic of Cameroon and national identification with the Republic of Ambazonia. Implications and opportunities for further research are discussed as well.